A Systematic Review of the Cost-Effectiveness of Nurse Practitioners and Clinical Nurse Specialists: What Is the Quality of the Evidence?. (31st August 2014) - Donald, Faith; Kilpatrick, Kelley; Reid, Kim; Carter, Nancy; Martin-Misener, Ruth; Bryant-Lukosius, Denise; Harbman, Patricia; Kaasalainen, Sharon; Marshall, Deborah A.; Charbonneau-Smith, Renee; Donald, Erin E.; Lloyd, Monique; et al.
Abstract : Background . Improved quality of care and control of healthcare costs are important factors influencing decisions to implement nurse practitioner (NP) and clinical nurse specialist (CNS) roles. Objective . To assess the quality of randomized controlled trials (RCTs) evaluating NP and CNS cost-effectiveness (defined broadly to also include studies measuring health resource utilization). Design . Systematic review of RCTs of NP and CNS cost-effectiveness reported between 1980 and July 2012. Results . 4, 397 unique records were reviewed. We included 43 RCTs in six groupings, NP-outpatient (n = 11 ), NP-transition (n = 5 ), NP-inpatient (n = 2 ), CNS-outpatient (n = 11 ), CNS-transition (n = 13 ), and CNS-inpatient (n = 1 ). Internal validity was assessed using the Cochrane risk of bias tool; 18 (42%) studies were at low, 17 (39%) were at moderate, and eight (19%) at high risk of bias. Few studies included detailed descriptions of the education, experience, or role of the NPs or CNSs, affecting external validity. Conclusions . We identified 43 RCTs evaluating the cost-effectiveness of NPs and CNSs using criteria that meet current definitions of the roles. Almost half the RCTs were at low risk of bias. Incomplete reporting of study methods and lack of details about NP or CNS education, experience, and role create challenges in consolidating the evidence of the cost-effectiveness of these roles.